The effect of e-payment and e-commerce on shopping trips in Malaysia - Armand Irfan Suhantoro, 1981- 613273; Kamalahasan Achu, supervisor 325910; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2018